Comparative Economic and Clinical Utility of Adding Candesartan for Hypertension Management - Najmiatul Fitria; Thang Nguyen; Afifah Machlaurin; Nabila Al Rizka; Dian Ayu Juwita (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Introduction: Antihypertensive drugs require high costs because they are used over a long period. Therefore, consideration is needed in drug selection requirements, effectiveness, and price. This study aimed to see the beneficial results of hypertension therapy and the non-medical costs incurred by patients using cost-utility analysis (CUA). Method: This research was a prospective study. The incremental Cost-Utility Ratio (ICUR) of antihypertensive treatment was calculated using cost-utility data obtained through EQ-5D-5L questionnaires from outpatients at Universitas Andalas Hospital in January- March 2023 who met the inclusion and exclusion criteria. The costs used were from a patient perspective, consisting of direct medical and non-medical costs. This study compared standard treatment (amlodipine) with the addition of candesartan. Results: The number of respondents in this study was 67, consisting of 23 respondents (34.33%) using amlodipine alone and 44 respondents (65.67%) using the amlodipine-candesartan combination. The ICUR value obtained was IDR7,318,674/QALY. The difference in the average utility value of the amlodipine-candesartan combination with amlodipine alone is -0.02, and the difference in cost is -IDR12,224. Based on the cost-utility diagram, the amlodipine-candesartan combination group is included in the southwest quadrant (quadrant III), which illustrates that the cost required for the amlodipine-candesartan combination group is lower than the cost of the amlodipine single treatment group and the outcome is also not better (slightly lower or the same). Conclusion: It was recommended to prioritize using amlodipine alone for hypertension management, as it provides similar outcomes to the amlodipine-candesartan combination while incurring lower costs.